2015
DOI: 10.1002/tesq.249
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation of Meaning Strategies in Child EFL Mainstream and CLIL Settings

Abstract: Research on child English as a second language (ESL) learners has shown the benefits of task-based interaction for the use of different negotiation of meaning (NoM) strategies, which have been claimed to lead to second language learning. However, research on child interaction in foreign language settings is scarce, specifically research on a new prevalent methodology in Europe, content and language integrated learning (CLIL). The present study focuses on mainstream and CLIL English as a foreign language (EFL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 29 publications
(75 reference statements)
8
33
4
Order By: Relevance
“…García Mayo and Lázaro Ibarolla (2015) compared mainstream and CLIL classrooms (8-9 and 10-11 year olds) and found that CLIL groups used more clarification requests and repetition and relied less on L1 than the mainstream learners. Azkarai and Imaz Agirre (2016), building on the previous study and conducting research with the same group of children a year later, found, somewhat surprisingly, that all children negotiated meaning but the older children employed significantly fewer strategies than the younger children. The authors concluded that the tasks were probably too easy for the older groups thus their interactions required fewer negotiation moves.…”
Section: Task-based Studies With Young Learnersmentioning
confidence: 66%
“…García Mayo and Lázaro Ibarolla (2015) compared mainstream and CLIL classrooms (8-9 and 10-11 year olds) and found that CLIL groups used more clarification requests and repetition and relied less on L1 than the mainstream learners. Azkarai and Imaz Agirre (2016), building on the previous study and conducting research with the same group of children a year later, found, somewhat surprisingly, that all children negotiated meaning but the older children employed significantly fewer strategies than the younger children. The authors concluded that the tasks were probably too easy for the older groups thus their interactions required fewer negotiation moves.…”
Section: Task-based Studies With Young Learnersmentioning
confidence: 66%
“…They also found CLIL learners used their L1 to a lesser extent than mainstream learners. Azkarai and Imaz Agirre (2016) argued that the difference between their study and García Mayo and Lázaro Ibarrola's (2015) study could be because in their study they considered two tasks, whereas García Mayo and Lázaro Ibarrola considered only one.…”
Section: Different Instructional Settings and Types Of Learnersmentioning
confidence: 90%
“…Yet it has been shown that just as differences exist between adults and children, so do differences between younger and older child learners. Age differences for children have been found in interaction studies (e.g., in ESL settings: Oliver, 1998, 2002, 2009; in EFL settings: Azkarai & García Mayo, 2016; Azkarai & Imaz Agirre, 2016; Butler & Zeng, 2014, 2015; García Mayo & Lázaro Ibarrola, 2015), particularly in relation to task use (e.g., in ESL settings: Oliver, 1995, 1998, 2002; in EFL settings: Azkarai & Imaz Agirre, 2016) and task repetition (e.g., in ESL settings: Mackey et al, 2007; in EFL settings: Azkarai & García Mayo, 2016; García Mayo & Imaz Agirre, 2016).…”
Section: Age and Child Slamentioning
confidence: 97%
See 1 more Smart Citation
“…Astonishingly, even though there are indications that strategy use affects language learning success and despite claims that learner strategies are key to learner autonomy and knowledge construction in content and integrated learning (Wolff: 2004), research on the effect of learner strategies on successful CLIL learning and performance is very sparse. There are only a few intervention studies (Azkarai & Agirre 2015, Jaekel: 2015, Lorenzo & Moore 2010, Meyer 2013; Ruiz de Zarobe & Zenotz 2015) published to date. However, here seems to be a growing consensus that what is needed to assess the effect of instructed strategy use on learner performance is a reconceptualization of the construct of learner strategies not as traits but as techniques which can be taught and learned, and which are accessible to reflection and subsequent modification so that they can be used deliberately and purposefully and thus become learner strategies for individual learners (Schmenk 2009: 84/85).…”
Section: Ii4 Learner Strategiesmentioning
confidence: 99%